2004
DOI: 10.1038/nsmb746
|View full text |Cite
|
Sign up to set email alerts
|

p27 binds cyclin–CDK complexes through a sequential mechanism involving binding-induced protein folding

Abstract: p27 controls cell proliferation by binding and regulating nuclear cyclin-dependent kinases (CDKs). In addition, p27 interacts with other nuclear and cytoplasmic targets and has diverse biological functions. We seek to understand how the structural and dynamic properties of p27 mediate its several functions. We show that, despite showing disorder before binding its targets, p27 has nascent secondary structure that may have a function in molecular recognition. Binding to Cdk2-cyclin A is accompanied by p27 foldi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
408
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(428 citation statements)
references
References 52 publications
19
408
0
1
Order By: Relevance
“…Hydrodynamic and spectroscopic analyses indicate that human p57 Kip2 lacks a stable helical and b-sheet structure, although the formation of a secondary structure cannot be precluded (50). On the basis of these findings, p57 Kip2 joins the most-investigated p27 Kip1 and its sibling p21 Cip1 in being considered highly unfolded molecules (51)(52)(53)(54).…”
Section: P57 Kip2 Proteinmentioning
confidence: 99%
“…Hydrodynamic and spectroscopic analyses indicate that human p57 Kip2 lacks a stable helical and b-sheet structure, although the formation of a secondary structure cannot be precluded (50). On the basis of these findings, p57 Kip2 joins the most-investigated p27 Kip1 and its sibling p21 Cip1 in being considered highly unfolded molecules (51)(52)(53)(54).…”
Section: P57 Kip2 Proteinmentioning
confidence: 99%
“…Some well-known examples include the phosphorylated kinase-inducible domain (pKID) of the cAMP responsive element binding protein (CREB), 1 the transcriptional activation domain structural preferences. For example, NMR studies demonstrated that the linker helix of p27 Kip1 has a nascent secondary structure in its free state 4 although it is largely unstructured in solution. 5 It is increasingly apparent that residual structure of IUPs plays crucial roles in molecular recognition.…”
Section: Introductionmentioning
confidence: 99%
“…At high concentration of competing ligand, k obs will approach k off . There are several methods available to measure rate constants of which the currently most common for IDPs (and folded proteins) are stopped-flow spectroscopy 6 and surface plasmon resonance, 7 but temperature jump, 8 and fluorescence correlation spectroscopy 9 have also been used. NMR transverse relaxation dispersion 10,11 has also emerged as a powerful method to obtain site resolved information about the thermodynamics, kinetics, and chemical shift differences for proteins undergoing conformational exchange on the µs-ms timescale.…”
Section: Introductionmentioning
confidence: 99%